Biomechanical Characterization of Endothelial Cells Exposed to Shear Stress Using Acoustic Force Spectroscopy - Silvani, Giulia; Romanov, Valentin; Cox, Charles D.; Martinac, Boris (Frontiers in Bioengineering and Biotechnology, 2021)
Characterizing mechanical properties of cells is important for understanding many cellular processes, such as cell movement, shape, and growth, as well as adaptation to changing environments. In this study, we explore the mechanical properties of endothelial cells that form the biological barrier lining blood vessels, whose dysfunction leads to development of many cardiovascular disorders. Stiffness of living endothelial cells was determined by Acoustic Force Spectroscopy (AFS), by pull parallel multiple functionalized microspheres located at the cell-cell periphery. The unique configuration of the acoustic microfluidic channel allowed us to develop a long-term dynamic culture protocol exposing cells to laminar flow for up to 48 h, with shear stresses in the physiological range (i.e. 6 dyn/cm2). Two different Endothelial cells lines, Human Aortic Endothelial Cells (HAECs) and Human Umbilical Vein Endothelial Cells (HUVECs), were investigated to show the potential of this tool to capture the change in cellular mechanical properties during maturation of a confluent endothelial monolayer. Immunofluorescence microscopy was exploited to follow actin filament rearrangement and junction formation over time. For both cell types we found that the application of shear-stress promotes the typical phenotype of a mature endothelium expressing a linear pattern of VE-cadherin at the cell-cell border and actin filament rearrangement along the perimeter of Endothelial cells. A staircase-like sequence of increasing force steps, ranging from 186 pN to 3.5 nN, was then applied in a single measurement revealing the force-dependent apparent stiffness of the membrane cortex in the kPa range. We also found that beads attached to cells cultured under dynamic conditions were harder to displace than cells cultured under static conditions, showing a stiffer membrane cortex at cell periphery. All together these results demonstrate that the AFS can identify changes in cell mechanics based on force measurements of adherent cells under conditions mimicking their native microenvironment, thus revealing the shear stress dependence of the mechanical properties of neighbouring endothelial cells.